KEPEMIMPINAN KIAI DALAM MELAKUKAN INOVASI PENDIDIKAN DI PESANTREN - Heridianto, Heridianto (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This study aims to determine the concept, strategy of kiai leadership and obstacles in innovating education in pesantren. This research is a qualitative research case study. The research location chosen was at the Salafiyah Al-Ottoman Islamic Boarding School Beddian Jambesari Jambesari Darus Sholah Bondowoso, because it has a uniqueness compared to Islamic boarding schools in general, which is still maintaining traditional educational patterns reflected in the curriculum that teaches classical books. Data collection using observation, interviews, and documentation. Analysis techniques use the process of data condensation, data presentation, and conclusions. This study found that the concept of kiai leadership in innovating education in pesantren is based on vertical communication (downward communication-upward communication), horizontal communication and diagonal communication (cross communication). Meanwhile, the strategies carried out by the kiai in innovating education are: opening an open junior high school, alleviating a 9-year compulsory education program for Salaf Islamic boarding schools and opening a formal madrasah. There are four obstacles inhibiting the leadership of the kiai, namely: at first the family council was less supportive with formal education; lack of support from Old Alumni of PPs Al-Utsmani Beddian, the lack of Human Resources and infrastructure owned is still inadequate.